Bimbingan Spiritual untuk Meningkatkan Coping Stress dalam Pandemi Covid-19 pada Pengajian ‘Aisyiyah Ranting Kereng Bengkirai - Lilik Kholisotin; Sadar Sadar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Coronavirus or severe acute respiratory syndrome coronavirus 2 is a virus that attacks the respiratory system. This disease due to viral infection is called COVID-19. The Coronavirus can cause minor disturbances to the respiratory system, severe lung infections, and death. The rapid spread of the coronavirus has caused fear, anxiety, and several other social problems in the community. Besides, the implementation of various government policies to break the chain of distribution of COVID 19, on the other hand, has had a negative impact. This community service aims to provide education to the community, especially in the teaching group Aisyiyah Kereng Bangkirai in the form of socialization and spiritual guidance to reduce anxiety and worry about Covid-19. The implementation method offered is spiritual guidance to deal with stress problems due to the Covid-19 pandemic by delivering material from an Islamic religious perspective and a psychological perspective. The results of this dedication show that there is anxiety among the community due to Covid-19 which has a psychological impact and that impact also affects the joints of community life, both socio-economic, socio-cultural, and socio-religious. Based on the results of the activities carried out, it can be concluded that community service activities can have a positive impact on society regarding the anxiety arising from the Covid-19 pandemic, as well as providing an understanding that religion is always relevant to all conditions that arise in society. Religion is not something rigid but something elastic so that it can always provide solutions to problems that arise.